GWAS Follow-up Study Discovers a Novel Genetic Signal on 10q21.2 for Atopic Dermatitis in Chinese Han Population - Cai, Xin-Ying; Cheng, Lu; Yu, Chong-Xian; Wu, Yan-Yan; Fang, Ling; Zheng, Xiao-Dong; Zhou, Fu-Sheng; Sheng, Yu-Jun; Zhu, Jun; Zheng, Jie; Wu, Yuan-Yuan; Xiao, Feng-Li (Frontiers in Genetics, 2019)
Atopic dermatitis (AD) is a common inflammatory skin disease with high heritability. Two susceptibility loci have been confirmed in our previous AD genome-wide association study (GWAS). To look for additional genetic factors in Chinese Han ethnicity, we performed a large-scale GWAS follow-up study. Forty-nine top single nucleotide polymorphisms (SNPs) that had never been reported previously were genotyped using Sequenom Massarray system in an independent cohort, which consist of northern Chinese (1634cases and 1263controls) and southern Chinese (2985cases and 9526controls). Association analyses were performed using PLINK 2 software. Three SNPs in northern and ten SNPs in southern were found exhibiting association evidence with AD (P < 0.05). Finally, SNP rs224108 on 10q21.2 showed high significance for AD in joint analysis of GWAS and replication study (Pmeta = 4.55 × 10-9, OR = 1.21), and was confirmed as an independent genetic marker by Linkage disequilibrium calculation and conditional logistic regression analysis. Bioinformatics analysis strongly suggested that rs224108 may have the potential to alter the target gene expression through non-coding epigenetic regulation effects. Meanwhile, SNP rs11150780 on 17q25.3 was also found suggestive association with AD (Pmeta = 7.64 × 10-7, OR = 1.18). Our findings confirmed a novel susceptibility signal on 10q21.2 for AD in Chinese Han population and advanced the understanding of the genetic contribution to AD.